PENGEMBANGAN BUKU TEKS BERBASIS NASIONALISME DENGAN METODE VALUE CLARIFICATION TECHNIQUE (VCT) - Intan Kurniasari Suwandi dan Indah Perdana Sari (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2019)
AbstractThis research aimed to (1) produce textbook based on nationalism using suitable VCT method for students, and (2) examine the effectivity of textbook based on nationalism by using VCT method to improve nationalism understanding of elementary school students.This study is a Research and Development (R & D) with a Brog and Gall model.The validation of products involved 2 experts. The tryout involved 27 students of grade II in Trirenggo I Elementary School through three trials, that preliminary field testing, main field testing, and operational field testing. The data were collected through assessment sheet products,interview, observation, and questionnaire. The data were analyzed with independent sample t test at significance level of 0.05. The results of the study showthat textbook based on nationalism using VCT methode are foasible to use with the â€œvery goodâ€ eligibility criteria. The effectiveness is reviewed from the result of t-test and students respon analysis.The results of observations of nationalism character values before and after the study. While the result of the students responds analysis data after using textbook developed from the content of feasibility aspects are categorized as â€œvery goodâ€.Keywords: textbook, nationalism, VCT method